Ghost in the Machine: Daily Interaction with Ephemeral Computing - Sofia Pirandello (Cinergie)
The aim of this paper is to examine the phenomenon of the progressive spectralisation of the physical world, which involves a growing habit of contactless interaction. Indeed, the computerisation of domestic and social environments is almost complete. To realise this project of ubiquitous “spatial computing”, technology companies are converging on the development of wearable tools, mostly augmented reality (AR) glasses. While wearing them, users manipulate responsive but intangible objects that they “evoke” and that can appear ghostly from a distance. The interactive images of smart glasses are not concrete: they are digital entities that appear on the user’s lenses and respond to their voice commands and movements thanks to pattern recognition algorithms. Characterised by an unprecedented level of responsiveness, AR is a form of “total cinema” made up of 3D images that inhabit physical contexts. I will therefore refer to AR as a contemporary example of a portable phantasmagoric dispositif, a technology that involves the coexistence of people and images in the same space in real time. Finally, I will argue that, while the physical dimension is undergoing a progressive “ghostification”, it is not being replaced: in order to function, wearable technologies must be innervated in a human body, integrating eyes, hands, feet and emitted sounds as essential components for their operation. The current trend in technology, then, is to replace the touch revolution with a deeper performative turn that involves the user from head to toe.